Educação ambiental como instrumento de gestão na RESEX Mapuá: mediações para o desenvolvimento local - LEITE, Etiene Lobato (Universidade Federal do Pará, 2018)
This study results of a research in a conservation unit in the municipality of Breves, archipelago of Marajó, state of Pará. Its starting point is these questions: how does the relationship between environmental education and conservation unit management takes place? Does it converge to strengthen participatory practices of sustainable environmental development of the conservation unit? The attempt to build answers demanded a research survey whose main objective was to identify and analyze to what extent the relationship between environmental education and management contribute to meeting social and democratic commitments reflecting public action of schools, neighborhood association and council and meet the principles of creation of a conservative unit. Fulfilling this aim required to characterize the educational space in conservative unit; to check out whether environmental education practiced corresponds to the social and environmental development project in progress and how environmental education is included in the qualification process of the local population in order to participate (school governing board and neighborhood association). Data comes from questionnaires with open questions and semi-structured interviews, observation, and document. The research shows that the relationship between environmental education and management in a conservative unit is still incipient. Really there are possible paths, but they convergence. There are actions that shape the role of formal education — represented by schooling — and of non formal one — activities developed by ICMBio. But there is no dialogue between education intentions. Educational practices present in the conservative unit must adapt their pedagogy to meet local demands — content must be contextualized so that learning can be (res)signified based on "knowledge and nature" and focused on a life based on elements provided by the "forest and the waters" and valuing cultural and occupational practices. Possibilities of making it to establish are still must converge. Therefore, school, inhabitants and their association, public departments, councils, and other interested parties present in the conservative unit need combining efforts: environmental care, community organization, education integrated to the environment, and participatory management.